Mengamati Bintang, Pengetahuan Merespon Bencana: Belajar dari Tuntunan Para Leluhur di Sinar Resmi Sukabumi - Yeni Mulyani Supriatin Yeni (Fakultas Seni Rupa dan Desain ITB, 2023)
Agricultural practices must consider seasonal variations and natural conditions. Astronomy, which involves studying celestial movements, plays a crucial role in this regard. Individuals who possess the knowledge to decipher celestial motions have historically contributed to the advancement of civilizations worldwide. Consequently, the presence of astronomers specializing in astrology is essential. The global agricultural civilization experienced rapid growth before the emergence of the industrial civilization. In the current era of globalization, traditional agricultural systems based on astronomical observations are being abandoned. The adoption of foreign planting techniques has led to a neglect of the indigenous wisdom and knowledge passed down through generations. Over time, our ancestors’ local knowledge has gradually faded away. However, the indigenous people of Sinar Resmi, Sukabumi, continue to rely on star observations in their rice farming practices, particularly as a response to natural disasters. This study aims to demonstrate that rice farmers can effectively respond to natural disasters by observing the stars. It employs an oral tradition approach to describe the role of star observations in rice farming, focusing on case studies from the Sinar Resmi community in Sukabumi and other indigenous populations. The findings suggest that star observations in rice farming remain relevant for mitigating the risk of crop failure during natural disasters. The significance of astronomical observations and their inherent value lies in their ability to maintain order and stability in agrarian societies.